Perplex of Management Accounting and Information Systems - Jukka Heikkilä (Turun yliopisto, 2022)
We information systems researchers want to always pin point the contribution of professor Markus Granlund’s seminal research on management accounting and accounting IS. I’ll not make an exception, but would like to also share my view on the recent development in providing information for management accounting, or control, form our recent experiences of abductive research on ISs on the field.
A DEAN, A SCHOLAR, A FRIEND: Texts in appreciation of Markus Granlund